A historical review of the evolution of the Tardieu Scale. (16th April 2018) - Morris, Susan Louisa; Williams, Gavin
ABSTRACT: There are many clinical assessment tools that can be used to quantify spasticity, one feature of the Upper Motor Neurone (UMN) syndrome. The focus of this short paper is on three; the Tardieu Scale, the Modified Tardieu Scale and the Australian Spasticity Assessment Scale, because a fundamental concept of these tests is their velocity dependent nature. Other bedside assessments such as the Modified Ashworth Scale examine hypertonicity, another feature of the UMN syndrome, but in this instance, the stretching movement is not velocity dependent. The Tardieu Scale, while not officially named until 1997, was conceived in the 1950s and since that time it has been revised by multiple authors and it is these additions that will be discussed in this article. The advantages and disadvantages of these assessment tools will be discussed with the ultimate aim of identifying one that has greater clinical utility.